Temperamental exuberance and executive function predict propensity for risk-taking in childhood - Lahat, Ayelet (Dev Psychopathol, 2012)
The present study takes a multilevel approach to examine developmental trajectories in risk-taking propensity. We examined the moderating role of specific executive function components, attention shifting and inhibitory control, on the link between exuberant temperament in infancy and propensity for risk-taking in childhood. Risk-taking was assessed using a task previously associated with sensation seeking and antisocial behaviors. Two hundred and ninety one infants were brought into the lab and behaviors reflecting exuberance were observed at 4, 9, 24, and 36 months of age. Executive function was assessed at 48 months of age. Risk-taking propensity was measured when children were 60 months of age. The results indicate that exuberance and attention shifting, but not inhibitory control, significantly interact to predict propensity for risk-taking. Exuberance was positively associated with risk-taking propensity among children relatively low in attention shifting but unrelated for children high in attention shifting. These findings illustrate the multifinality of developmental outcomes for temperamentally exuberant young children and point to the distinct regulatory influences of different executive functions for children of differing temperaments. Attention shifting likely affords a child the ability to consider both positive and negative consequences, and moderates the relation between early exuberance and risk-taking propensity.